Reflections on Culture, Dialogue and Traveller at the International Students Workshop in Florence - Gabija Bankauskaitė (Respectus Philologicus, 2018)
Do you enjoy traveling? Probably there is no person with a negative response. Some of travellers are fast collectors of famous places, while others are just observers of culture and lifestyle. The third ones simply lost in tourism gaining popularity on social networks, while some like to travel on a virtual basis... But let us just imagine positive tourism which really helps to preserve cultural and historical values. Why are some countries already protecting themselves form tourists? Finally, just ask yourself what kind of tourist are you? an active user? a philosophical custodian? a passive observer? The Romualdo Del Bianco Foundation (Fondazione Romualdo Del Bianco®) gives the answers to these and many other questions. The foundation cares about the values and responsibility of tourism philosophy. The International Institute Life Beyond Tourism® promotes the transformation of tourism into meaningful travel. It motivates the consumer of commercial tourism to reflect on the cultural and philosophical value of travel and traveler.